IMPLEMENTATION OF REFORMS IN THE FIELD OF PERSONNEL TRAINING IN THE HEALTHCARE SYSTEM OF THE FERGANA VALLEY - Ahmedova Rashida Muqimovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes the processes of organizing personnel training in the healthcare system during the years of Uzbekistan’s independence, the existing problems, and the stages of development of personnel of this system in the Fergana region. Also, the issues of personnel of the healthcare system in Fergana region are analyzed through the decisions and periodical press materials related to the field. Also, the reforms created in the healthcare system in our country are scientifically studied